Exploring the role that teacher characteristics and multi-dimensional beliefs play in technology integration uptake for teaching and learning in the secondary mathematics classroom: a mixed methods approach - Bano-Rizzo, Marybeth Lao (Kansas State University, 2024)
This study explored the role of secondary Mathematics teachers’ characteristics and multi-dimensional beliefs in integrating technology into teaching practice (i.e., mode of technology use). The research design employed is the convergent mixed method. The quantitative strand employed an electronic survey with 83 respondents. It has one primary question and four sub-questions, all about the relationship between the mode of technology use and each of the four predictor variables-teacher characteristics (gender, age, experience, education, grade level taught); beliefs about teaching with technology, self-efficacy beliefs, and epistemological beliefs all of which are measured in multi-level Likert scale. The qualitative strand employed a case study approach with four teacher participants. The data collection included an initial interview, a semi-structured follow-up interview, and classroom observation. The significant findings include that discovering learning (constructivist practices) is the primary mode of technology use. The driving force behind this phenomenon is multidimensional, including teacher self-efficacy beliefs, beliefs about teaching with technology, and teacher pedagogical beliefs. Teacher age, experience, and educational level also play a role, but teacher characteristics, in general, do not play a pivotal role in the use of technology in the mathematics classroom.
Keywords: Technology (i.e., digital mathematical technologies); Role of teacher beliefs; Discovery learning (active learning); Technology for discovery/active learning